Human myometrial artery function and endothelial cell calcium signalling are reduced by obesity: Can this contribute to poor labour outcomes?. (1st August 2019) - Prendergast, Clodagh; Wray, Susan
Abstract: Aims: Determining how obesity affects function in human myometrial arteries, to help understand why childbirth has poor outcomes in obese women. Methods: Myometrial arteries were studied from 84 biopsies. Contraction (vasopressin and U‐46619) and relaxation (carbachol, bradykinin, SNAP) was assessed using wire myography. eNOS activity was assessed using L‐NAME. Cholesterol was reduced using methyl‐β‐cyclodextrin to determine whether it altered responses. Differences in endothelial cell intracellular Ca 2+ signalling were assessed using confocal microscopy. Results: The effects of BMI on relaxation were agonist specific and very marked; all vessels, irrespective of BMI, relaxed to bradykinin but 0% of vessels (0/13) from obese women relaxed to carbachol, compared to 59% (10/17) from normal weight women. Cholesterol‐lowering drugs did not restore carbachol responses (n = 6). All vessels, irrespective of BMI, relaxed when NO was directly released by SNAP (n = 19). Inhibition of eNOS with L‐NAME had a significant effect in normal but not overweight/obese vessels. Compared to bradykinin, a lower proportion of endothelial cells responded to carbachol and the amplitude of the calcium response was significantly less, in all vessels. Furthermore, a significantly lower proportion of endothelial cells responded to carbachol in the overweight/obese group compared to control. In contrast to relaxation, the effect of contractile agonists was unchanged with increasing BMI. Conclusions: The ability of human myometrial arteries to relax is significantly impaired with obesity, and our data suggest this is due to a deficit in endothelial calcium signalling. This inability to recover following compression during contractions, might contribute to poor labours in obese women.